Teacher Attrition and School Leaders’ Capacity for Leading, Practices and Behaviors – A Comparative Study - Gui, Gabriela E. (European Journal of Social Science Education and Research, 2024)
Teacher attrition, as part of the bigger issue of teacher shortage, has caused increasing concerns in the past decades for both policymakers and educational leaders. Its negative effects impact various aspects of a school. Historically struggling schools serving students in poverty areas are perennially and negatively affected by high turnover rates at deeper levels. Building on existing literature that examines the correlation between school contextual factors and teacher attrition, this study examines the responses of 300+ teachers from Western and Southeast Michigan, gathered through a 24-questions survey. Data was analyzed against the study’s research questions using the Cronbach’s alpha test and one-way ANOVA. For the first research question, the study looked at the effects of the school principal and his/her leadership capacity on the teachers’ decision to leave a school, a school district, or the teaching profession altogether. The second research question dealt with differences related to how teachers from various backgrounds were affected by the quality of their school principals and work environments. The findings support the study’s hypothesis that the principal's role in building a positive school culture, along with the principal's behaviors, practices, and leadership capacity significantly affect teacher satisfaction and retention. Some differences do exist with respect to how teachers from various grade levels are affected by their learning environments (including principal leadership), and to what organizational factors influence their decisions to stay.
Keywords: teacher attrition, retention, principal leadership